KESEIMBANGAN ENERGI DAN KOMPOSISI TUBUH PEKERJA DENGAN JENIS PEKERJAAN BERBEDA - Yuniar Rosmalina; Dewi Permaesih; Sri Martuti; Reviana Christiani; Susilowati Herman (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2005)
ABSTRACT Background: Energy is   a main source for doing daily activities. The energy is balance if the energy intake equal to energy expenditure. However energy expenditure depends on their kind of occupational work and their daily activities. The objective of this study is to assess the energy balance and body composition of male workers (light and heavy worker).  Methods: The subjects were 51 sandal workers considered as light level workers and 50 stone as heavy workers whose met criteria 30-55 years old, physically healthy and agreed to involve in this study. Body composition was measured using anthropometry. Anthropometric measurement was applied including body weight, height, MUAC and skin fold thickness. Nutrient intake was collected by combination weighing and 24 hours recall method for 3 consecutive days. Physical activities during working were assess by recording and recall their activities after doing their occupational activities, also for 3 consecutive days. Other data collection include physical examination by a medical doctor and interview was done to identified their characteristic and sosiodemografi. Results: The body fat composition was different significantly between light worker and heavy worker. The average energy and protein intake showed the heavy worker had lower both nutrient intakes compared to light workers. The average energy intake of light worker was 1923 ± 295 Kcal and 41.6 ± 8.99 g protein, while the energy and protein intake heavy worker was 2232 ± 500 Kcal and 46.7 ± 14.7 g protein. The energy expenditure of heavy worker was higher compared to light worker (3548 ± 414 Kcal vs 2408 ± 227 Kcal). There was no significant correlation between energy balance and body composition variables. Conclusions: Heavy male workers as well as light male workers have deficit energy and this no significant correlation with the body composition variable. [Penel Gizi Makan 2005,28(1): 1-8]. Keywords: energy, body composition, male worker